Formulation of Ebastine Fast-Disintegrating Tablet Using Coprocessed Superdisintegrants and Evaluation of Quality Control Parameters. (19th May 2022) - Dhakal, Bhawana; Thakur, Jaybir Kumar; Mahato, Reema Kumari; Rawat, Ishwori; Rabin, D. C.; Chhetri, Rahul Rana; Shah, Kedar Prasad; Adhikari, Atul; Pandey, Jitendra
Abstract : Ebastine is a long-acting, nonsedating, second-generation antihistaminic drug that prevents histamine action, mainly in immediate hypersensitivity. This project was aimed to formulate and characterize orodispersible tablets of ebastine, utilizing different proportions of three disintegrants, namely crospovidone, sodium starch glycolate, and coprocessed superdisintegrant. Initially, fifteen trial batches of ebastine orodispersible tablets were outlined using the central composite design of Minitab software. The tablets were formulated by the direct compression method. The compressed tablets were then evaluated for precompression and postcompression physicochemical parameters, such as angle of repose, Carr's index, Hausner's ratio, hardness, thickness, weight variation, drug content, friability, wetting time, disintegration time, dispersion time, and water absorption ratio. The in vitro dissolution test was conducted according to Indian Pharmacopeia 2018, with the help of the rotating paddle method using 0.5% w/v sodium lauryl sulfate buffer in 0.1 N HCl. For the optimized batch (8 th batch), all the physicochemical parameters like angle of repose (33.77°), Carr's index (19.34%), Hausner's ratio (1.24), weight variation (202.5 mg), hardness (4.3 kg/cm 2 ), friability (0.44%), thickness (3.16 mm), dissolution (95.78%), and drug content (101.67%) were within the acceptable limit as per Indian Pharmacopeia 2018. The wetting time, disintegration time, dispersion time, and water absorption ratio were reported to be 25.1 seconds, 16.0 seconds, 38.6 seconds, and 91.92%, respectively. Hence, the results suggested that orodispersible tablets of ebastine can be formulated. Furthermore, the mixing of crospovidone, sodium starch glycolate, and coprocessed super disintegrants can result in excellent desirable properties in the orodispersible tablet.